Pretransplantation Donor–Recipient Pair Seroreactivity Against BK Polyomavirus Predicts Viremia and Nephropathy After Kidney Transplantation. Issue 1 (8th July 2016) - Wunderink, H. F.; van der Meijden, E.; van der Blij‐de Brouwer, C. S.; Mallat, M. J. K.; Haasnoot, G. W.; van Zwet, E. W.; Claas, E. C. J.; de Fijter, J. W.; Kroes, A. C. M.; Arnold, F.; Touzé, A.; Claas, F. H. J.; et al.
Abstract : Kidney transplant donors are not currently implicated in predicting BK polyomavirus (BKPyV) infection in kidney transplant recipients. It has been postulated, however, that BKPyV infection originates from the kidney allograft. Because BKPyV seroreactivity correlates with BKPyV replication and thus might mirror the infectious load, we investigated whether BKPyV seroreactivity of the donor predicts viremia and BKPyV‐associated nephropathy (BKPyVAN) in the recipient. In a retrospective cohort of 407 living kidney donor–recipient pairs, pretransplantation donor and recipient sera were tested for BKPyV IgG levels and correlated with the occurrence of recipient BKPyV viremia and BKPyVAN within 1 year after transplantation. Donor BKPyV IgG level was strongly associated with BKPyV viremia and BKPyVAN (p < 0.001), whereas recipient BKPyV seroreactivity showed a nonsignificant inverse trend. Pairing of high–BKPyV‐seroreactive donors with low‐seroreactive recipients resulted in a 10‐fold increased risk of BKPyV viremia (hazard ratio 10.1, 95% CI 3.5–29.0, p < 0.001). In multivariate analysis, donor BKPyV seroreactivity was the strongest pretransplantation factor associated with viremia (p < 0.001) and BKPyVAN (p = 0.007). The proportional relationship between donor BKPyV seroreactivity and recipient infection suggests that donor BKPyV seroreactivity reflects the infectious load of the kidney allograft and calls for the use of pretransplantation BKPyV serological testing of (potential) donors and recipients. Abstract : In this retrospective cohort study, the authors find pretransplantation donor–recipient pair BK polyomavirus seroreactivity predicts viremia and nephropathy after kidney transplantation.